mTOR inhibitor INK128 promotes wound healing by regulating MDSCs - Li, Yi (Stem Cell Res Ther, 2021)
BACKGROUND: Skin wounds in diabetic patients hardly recover. Accumulating evidence has shown that mammalian target of rapamycin (mTOR) pathway and myeloid-derived suppressor cells (MDSCs) are involved in inflammatory-related response. INK128 is a novel mTOR kinase inhibitor in clinical development. However, the exact roles of MDSCs and INK128 in healing wound of diabetic patients are unclear. METHODS: Mice models of normal, diabetic, and diabetic+INK128 were constructed. Bone marrow (BM)-derived macrophages and RAW264.7 cell line co-cultured with MDSCs, which were induced at different conditions. Flow cytometry, western blot, quantitative real-time PCR, and immunohistochemical analysis were performed. RESULTS: Diabetic mice (DM) had a slower recovery rate, thinner epidermis and dermis, and less blood vessels than those of normal mice. MDSCs were abnormally accumulated in DM, mTOR was activated in MDSCs of DM, and the cells were treated with high glucose. Moreover, mTOR signaling inhibitor INK128 could promote wound healing through reducing the MDSCs. MDSC function was disordered in DM and high-glucose environments, while INK128 could help retrieve their function. Furthermore, high glucose and other factors in DM could promote M-MDSC differentiation to M1 pro-inflammatory macrophage cells, thus inhibiting wound healing. The differentiation, which was dependent on mTOR signaling, could be reversed by INK128. CONCLUSION: INK128 is potential to be developed as a clinical strategy to promote wound healing of diabetic patients.